The Development of Effective Communication Skills Instruments: Identification of Student Communication Skills - Iqbal Miftakhul Mujtahid, Mery Berlian, Rian Vebrianto, Musa Thahir (International Journal of Advanced Science and Technology, 2020)
As part of the Demographic Dividend, students must maintain effective communication skills to welcome the MEA (ASEAN Economic Community). The study aims to develop communication skills instruments that have high effectiveness, validity, and reliability to measure the optimum functions of communication skills in students. This study refers to enGauge 21st-century skills to analyze the effectiveness of communication skills by involving five constructs such as 1) working in groups/teams, 2) interpersonal skills, 3) integrity, 4) responsibility, and 5) interactive communication. The researchers adapted the questionnaire method by compiling each construct justified and agreed upon by experts. This research study is a survey of 200 respondents of non-primary education students at the Universitas Terbuka, Pekanbaru, Riau, selected through stratified sampling and random sampling. The data were then analyzed using SPSS version 18.00 for Windows, while internal consistency was investigated with Cronbach’s Alpha. The results of the analysis confirm the validity and reliability of effective communication skills with Cronbach’s Alpha scores 0.803 - 0.816. Thus, this research succeeded in producing high-quality instruments, so it is useful to evaluate the effectiveness of student communication skills.